Detection of Structural Defects in Fabric Parts Using a Novel Edge Detection Method. (1st December 2018) - Dhivya, M; Renuka Devi, M
Abstract: A fabric fault detection scheme is implemented in this work using frame harmonizing-based approach. Many recent research works deliver the fabric defect detection techniques. But in the textiles industry, the fast process of fabric cutting and sewing, lots of auxiliary imperfections have emerged. Particularly these defects cannot be identified easily by experts as well as an automated system. In our system, a novel frame extraction technique is used to find the defects in the fabric production pipeline. The input fabric image frame is pre-processed by transformation and filtering techniques. In this work, a novel multi-directional and multi-scale outline extraction method is proposed to extract the edge map. Contour-based features are extracted and classified by K-nearest neighbor classifier. The experimentation with real-time dataset produced the outstanding performance results when compared with state of the art methods.